Synthesis, Characterization and Antimicrobial Activity of Metal Chelates of 5-[1(H)-Benzotriazole methylene]-8-quinolinol - H. S. Patel; K. K. Oza (E-Journal of Chemistry)
5-Chloromethyl-8-quinolinol was condensed stoichiometrically with benzotriazole in presence of potassium carbonate. The resulting 5-[1(H)-benzo triazole methylene]-8-quinolinol (BTMQ) was characterized by elemental analysis and spectral studies. The transition metal chelates viz. Cu2+, Ni2+, Co3+, Mn2+ and Zn2+ of BTMQ were prepared and characterized by metal-ligand (M:L) ratio, IR and reflectance spectral studies and magnetic properties. The antifungal activity of BTMQ and its metal chelates was screened against various fungi. The results show that all these samples are good antifungal agents.